2022
DOI: 10.4250/jcvi.2021.0185
|View full text |Cite
|
Sign up to set email alerts
|

The Usefulness of 4D Echocardiographic Modality for Assessing RV Affection in Uncontrolled Hypertensive Patients

Abstract: BACKGROUND In many cardiovascular disorders, the contractile performance of the right ventricle (RV) is the primary determinant of prognosis. For evaluating RV volumes and function, 4 dimensional (4D)-echocardiography has become common. This research used 2D and 4D modalities to assess RV contractile performance in hypertensive patients. METHODS A total of 150 patients with essential hypertension were enrolled in this study, along with 75 age and sex-matched volunteers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…To supplement the 2D echocardiography, 3D measurements are recommended as they provide more accurate data for quantification of LV volume, despite the limitations of lower temporal resolution and higher dependency on image quality [ 42 , 43 ]. The 3D echocardiographic modality is also useful for the evaluation of right ventricular volume and function [ 44 ].…”
Section: Evaluation Of Cardiovascular Diseases In Patients With Diabe...mentioning
confidence: 99%
“…To supplement the 2D echocardiography, 3D measurements are recommended as they provide more accurate data for quantification of LV volume, despite the limitations of lower temporal resolution and higher dependency on image quality [ 42 , 43 ]. The 3D echocardiographic modality is also useful for the evaluation of right ventricular volume and function [ 44 ].…”
Section: Evaluation Of Cardiovascular Diseases In Patients With Diabe...mentioning
confidence: 99%
“…As the author mentioned, hypertensive patients should be assessed for right heart involvement as well as left heart. 4) Whether these right heart changes occur early, at the same time as left heart changes due to interdependence of the two structures, or whether it is a secondary phenomenon possibly related to pulmonary vascular changes remains to be proven by further studies. For the evaluation of RV involvement in hypertensive patients, 4D echocardiographic assessment is more sensitive and comprehensive than 2D echocardiographic evaluation.…”
mentioning
confidence: 98%
“…However, previous studies showed RV dysfunction in untreated or mildly hypertensive patients using mainly 2-dimensional (2D) echocardiographic study. 4) This study represented a real clinical situation because enrolled patients had already been prescribed and taken the medications for at least 30 months.…”
mentioning
confidence: 99%